Evaluasi Kebijakan Disiplin PNS: Analisis PP 94/2021 di Kabupaten Sidoarjo - Sri Wahyuni; Ika Devy Pramudiana; Aris Sunarya (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study evaluates the implementation of Government Regulation Number 94 of 2021 concerning Civil Servant Discipline, assessing its impact on enhancing the effectiveness and accountability of public administration within Sidoarjo Regency. Civil servant discipline constitutes a critical instrument in bureaucratic reform oriented towards good governance and high-quality public services. This research employs a qualitative approach utilising William Dunn's policy evaluation model, which encompasses the dimensions of effectiveness, efficiency, adequacy, responsiveness, and appropriateness. Data were collected through documentary analysis of prevailing legislation, local government performance reports, SAKIP (Government Agency Performance Accountability System) reports, SPIP (Government Internal Control System) reports, and digital human resource management system documents. Data analysis was conducted qualitatively, employing source triangulation to ensure the validity of the findings. The evaluation results indicate that Government Regulation 94/2021 is effective in reducing work procedure deviations, enhancing public service consistency, and strengthening accountability through clear audit trails. Integration with the 'Smart ASN' (State Civil Apparatus) and 'e-Kinerja' (e-Performance) systems reinforces the objectivity of performance assessments and minimises subjectivity. However, challenges persist regarding aspects of organisational culture, supervisory capacity, and the quality of infraction documentation. This study concludes that consistent disciplinary enforcement, when integrated with performance management systems, serves as a driving force for bureaucratic effectiveness and accountability. It further accelerates the consolidation of regional bureaucratic reform, fostering a bureaucracy that is professional, maintains high integrity, and is responsive to societal needs.